Crystallographic and spectral equivalence of boron-carbide polymorphs. (September 2016) - Kunka, Cody; Awasthi, Amnaya; Subhash, Ghatu
Abstract: The extraordinary properties of boron carbide originate from the collection of polymorphs that comprise fabricated samples. However, traditional nomenclature that differentiates and describes these crystal structures often restricts the ability to fully model variations in material properties and performance. To highlight and transcend these limitations, this study introduces a modified nomenclature and defines new groups of equivalent polymorphs based on quantum-mechanical simulations. Trends in lattice parameters, total energy, and Raman spectra are explained in terms of the unique covalent-bonding environments of boron-carbide polymorphs. Graphical abstract: